Investigating the Existence of Gorontalo Customary Law in the National Criminal Code - Apripari Apripari; Vifi Swarianata; Jufryanto Puluhulawa; Irlan Puluhulawa; Dewi Nuramanah Matte (Dialogia Iuridica, 2023)
Through Article 2 paragraph (1) of Law of the Republic of Indonesia Number 1 of 2023 concerning the Criminal Code (National Criminal Code), customary law opportunities are open to existing through the prerequisites contained in the Explanation to Article 2 paragraph (1). For this reason, this study aims to determine the opportunities for the existence of Gorontalo customary law through the prerequisites contained in the Explanation of Article 2 paragraph (1) of the National Criminal Code. This research uses normative legal research methods with a statutory approach and conceptual approach and uses primary, secondary and tertiary legal materials. The legal material is then analyzed qualitatively using grammatical, systematic, and historical interpretations. The results showed that Gorontalo customary law exists through the presence of several regional regulations, including (1) Gorontalo Provincial Regulation Number 2 of 2016 concerning the Implementation of Customary Institutions; (2) Gorontalo Mayor Regulation Number 10 of 2020 concerning the Implementation of the Dulohupa Customary Institution of Gorontalo City; and (3) Regional Regulation of Bone Bolango Regency Number 8 of 2020 concerning the Implementation of Customary Institutions. Furthermore, through regulations at the regional level, Gorontalo customary law is also present through concrete events such as the management of customary institutions carried out periodically. Based on this, the regulation of concrete norms related to acts prohibited under living law in regional regulations as required by the Explanation to Article 2 paragraph (1) of the National Criminal Code will have a very large opportunity.